Pictures of the Rif War (1921-1927) in the illustrated press. The photograph as a communications element - Sánchez Vigil, Juan Miguel (Historia y Comunicación Social, 2021)
The Rif War (1921-1927) was covered in the press with an enormous amount of features and photographs. After the disaster at Annual (July, 1921), the different publications sent a large number of journalists and photo journalists to cover the “reconquering” and occupation of the territory. The photographs became a key communications element in the media and created an exceptional body of documentation. The purpose of this article is to analyze the photographs of the war appearing in six publications corresponding to the two leading news groups at the time: Prensa Española (Blanco y Negro and ABC) and Prensa Gráfica (Nuevo Mundo, Mundo Gráfico, La Esfera and El Sol). A total of 5,115 photographs have been recorded, most of them taken by a dozen top photo journalists, and it is clearly shown that the press offered a separate graphic report from the texts, which wielded a great deal of impact on public opinion.